Predictors of Prolonged Cardiopulmonary Exercise Impairment After COVID-19 Infection: A Prospective Observational Study - Vonbank, Karin; Lehmann, Antje; Bernitzky, Dominik; Gysan, Maximilian Robert; Simon, Stefan; Schrott, Andrea; Burtscher, Martin; Idzko, Marco; Gompelmann, Daniela (Frontiers in Medicine, 2021)
Objectives: Coronavirus disease 2019 (COVID-19) is a global pandemic affecting individuals to varying degrees. There is emerging evidence that even patients with mild symptoms will suffer from prolonged physical impairment. Methods: In this prospective observational study, lung function, and cardiopulmonary exercise testing have been performed in 100 patients for 3–6 months after COVID-19 diagnosis (post-CoVG). Depending on the severity of severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection, patients were divided into asymptomatic, or mild to moderate (mild post-CoVG), and severe post-CoVG [hospitalization with or without intensive care unit/non-invasive ventilation (ICU/NIV)]. Results have been compared with age, sex, and body mass index (BMI) matched control group (CG, N = 50). Results: Both lung function (resting) and exercise capacity (peak workload, Wpeak and peak oxygen uptake, VO2 peak - % predicted) were considerably affected in patients with severe post-CoV (81.7 ± 27.6 and 86.1 ± 20.6%), compared to the mild post-CoVG (104.8 ± 24.0%, p = 0.001 and 100.4 ± 24.8; p = 0.003). In addition, also the submaximal exercise performance was significantly reduced in the severe post-CoVG (predicted VT1/VO2 peak; p = 0.013 and VT2/VO2 peak; p = 0.001). Multiple linear regression analyses revealed that 74 % (adjusted R2) of the variance in relative VO2 peak of patients who had CoV could be explained by the following variables: lower age, male sex, lower BMI, higher DLCO, higher predicted heart rate (HR) peak, lower breathing reserve (BR), and lower SaO2 peak, which were related to higher relative VO2 peak values. Higher NT-proBNP and lower creatinine kinase (CK) values were seen in severe cases compared to patients who experienced mild CoV. Discussion: Maximal and submaximal exercise performance in patients recovering from severe COVID-19 remain negatively affected for 3–6 months after COVID-19 diagnosis. The presented findings reveal that impaired pulmonary, cardiac, and skeletal muscle function contributed to the limitation of VO2 peak in those patients, which may have important implications on rehabilitation programs.